Jaringan Saraf Tiruan Menjaga Keamanan Data dengan Metode Bidirectional Associative Memory - Yenni, Yusli (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2023)
System security is currently very much needed from irresponsible parties who damage and steal data. For this reason, a system is needed that is able to protect and secure data from criminal acts. The aim of this research is to provide data codes and keys using binary conversion using the Continuous BAM method. The Continuous BAM method, namely Bidirectional Associative Memory (BAM), has the ability to act as associative memory or content addressable memory, namely memory that can be called up using part of the information stored in it. Apart from that, the Bidirectional Associative Memory (BAM) Artificial Neural Network (ANN) has 2 layers and is fully connected from one layer to the other, so it is possible to have a reciprocal relationship between the input layer and the output layer. The final results of this research are 6 patterns that are entered into the search process, including number patterns 1, 3, 4, 5, 7, and 9 with input vector values of numbers 1 [16,-22], numbers 3 [20, 22], numbers 4 [16,-22], number 5 [20,6], number 7 [24,2] and number 9 [20,18], which do not match the pattern number 7. Requested target [1,-1], result obtained [1,1]. The Continuous Bam method can be used to detect patterns correctly and accurately.